Agenda for the third day of the 1976 Democratic National Convention (1976)
This document outlines the agenda for the third day of the 1976 Democratic National Convention on Wednesday, July 14. The evening session begins at 8:00 p.m. with an invocation, presentation of colors, and speeches by Democratic leaders, followed by the nomination of presidential candidates, a roll call vote, announcement of the nominee, a benediction, and recess around midnight. It also provides the first half of Governor Jimmy Carter's schedule for that day, including private meetings with the Labor Coalition, AFL-CIO Building Trades leadership, the executive committee of Governors, and the Latino Caucus, with additional activities expected to conclude by 5:00 p.m.